Plasmalemmal V-ATPase as a potential biomarker for lactoferrin-based anticancer therapy - Pereira, Cátia Sofia Santos (2022)
Lactoferrin (Lf) is a milk-derived protein with well-recognized potential as a therapeutic agent against a wide variety of cancers. This natural protein exhibits health-promoting effects and has several interesting features, including its selectivity towards cancer cells, good tolerability in humans, worldwide availability, and holding a generally recognized as safe (GRAS) status. To prompt the rational clinical application of this promising anticancer compound, previous works aimed to unveil the molecular mechanisms underlying its selective anticancer activity, where plasmalemmal V-ATPase was identified as an Lf target in cancer cells. V-ATPase is a proton pump critical for cellular homeostasis that migrates to the plasma membrane of highly metastatic cancer cells contributing to the acidity of the tumor microenvironment. Cancer cells were found to be susceptible to Lf only when this proton pump is present at the plasma membrane. Plasmalemmal V-ATPase can thus be an excellent biomarker for driving treatment decisions and forecasting clinical outcomes of Lf-based anticancer strategies. Future research endeavors should thus seek to validate this biomarker by thorough preclinical and clinical studies, as well as to develop effective methods for its detection under clinical settings.